2010
DOI: 10.1016/j.jcps.2010.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Communal and exchange relationship perceptions as separate constructs and their role in motivations to donate

Abstract: Researchers have operationalized communal and exchange relationship perceptions as either mutually exclusive categories or opposite ends of a continuum. This research conceptualizes these relationships as distinct constructs that should be measured separately. We develop multi-item measures of communal and exchange relationship perceptions and find that they are actually positively correlated. We also examine the way communal and exchange relationship perceptions combine to influence intrinsic, extrinsic, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 53 publications
1
71
0
1
Order By: Relevance
“…Consumers were asked to indicate which definition best represented their relationships with the performing arts center. While previous research has found that consumers can perceive a relationship that has elements of both exchange and communal relationships (Johnson & Grimm, ), most of the consumers were expected to perceive either the exchange component or communal component of their relationships to be stronger. By asking consumers to categorize themselves based on the dominant component of their relationships with the organization, the segmentation model based on the behavioral data was given the greatest opportunity to accurately identify consumers with different relationship perceptions.…”
Section: Study 1—segmentation Modelmentioning
confidence: 77%
See 2 more Smart Citations
“…Consumers were asked to indicate which definition best represented their relationships with the performing arts center. While previous research has found that consumers can perceive a relationship that has elements of both exchange and communal relationships (Johnson & Grimm, ), most of the consumers were expected to perceive either the exchange component or communal component of their relationships to be stronger. By asking consumers to categorize themselves based on the dominant component of their relationships with the organization, the segmentation model based on the behavioral data was given the greatest opportunity to accurately identify consumers with different relationship perceptions.…”
Section: Study 1—segmentation Modelmentioning
confidence: 77%
“…Consumer willingness to donate has also been shown to increase when the consumer–organization relationship shifts from an exchange relationship to a communal relationship (Aggarwal, ; Johnson & Grimm, ). Both communal and exchange relationships involve a long‐term orientation and ongoing interactions over time.…”
Section: Consumer Relationship Perceptions and Willingness To Donatementioning
confidence: 99%
See 1 more Smart Citation
“…Consumers in exchange relationships are more likely to seek utilitarian benefits (e.g., value for money or reciprocal exchange) since the relationship is based on input-output transaction value. Previous research found that people in a communal relationship were more satisfied with being underpaid (Peters and van den Bos, 2008) and more likely to donate (Johnson and Grimm, 2010) than those in an exchange relationship.…”
Section: The Moderating Effect Of Consumer-organization Relationship mentioning
confidence: 95%
“…Extant research has demonstrated that people with high (vs. low) communal orientation are more responsive to warmth perceptions (Scott, Mende, & Bolton, ) and are more willing to provide assistance to others (Clark et al., ). Similarly, it has been found that consumers in a communal brand relationship tend to genuinely desire the brand to succeed and engage in acts to help the brand (Johnson & Grimm, ). These findings associate communal orientation with people's intentions to help a warm brand.…”
Section: Study 3 Communal Orientationmentioning
confidence: 99%